2012
DOI: 10.1080/10962247.2012.748523
|View full text |Cite
|
Sign up to set email alerts
|

The Southeastern Aerosol Research and Characterization (SEARCH) study: Temporal trends in gas and PM concentrations and composition, 1999–2010

Abstract: The SEARCH study began in mid 1998 with a focus on particulate matter and gases in the southeastern United States. Eight monitoring sites, comprising four urban/nonurban pairs, are located inland and along the coast of the Gulf of Mexico. Downward trends in ambient carbon monoxide (CO), sulfur dioxide (SO 2 ), and oxidized nitrogen species (NO y ) concentrations averaged 1.2 AE 0.4 to 9.7 AE 1.8% per year from 1999 to 2010, qualitatively proportional to decreases of 4.7 to 7.9% per year in anthropogenic emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 26 publications
9
69
0
Order By: Relevance
“…These trends were attributed to pollution abatement strategies, downturn in the economy (which had a greater impact in Europe compared to the US) and unusual meteorological conditions. Ambient measurements in the southeastern US (Blanchard et al, 2013) show reductions in PM 2.5 of around 4.5 µg m -3 and SO 4 of 2.3 µg m -3 from 1999 to 2010 which is similar to that reported here. Controls on EGU and vehicle emissions is largely responsible for these decreases.…”
Section: Other Locationssupporting
confidence: 80%
See 3 more Smart Citations
“…These trends were attributed to pollution abatement strategies, downturn in the economy (which had a greater impact in Europe compared to the US) and unusual meteorological conditions. Ambient measurements in the southeastern US (Blanchard et al, 2013) show reductions in PM 2.5 of around 4.5 µg m -3 and SO 4 of 2.3 µg m -3 from 1999 to 2010 which is similar to that reported here. Controls on EGU and vehicle emissions is largely responsible for these decreases.…”
Section: Other Locationssupporting
confidence: 80%
“…There is a linear relationship between SO 2 emissions and ambient SO 4 with coefficients of determination above 0.89 for all sites. However, there is not quite a 1:1 proportional response in SO 4 to the SO 2 emissions reductions as previously observed in the Southeastern US (Blanchard et al, 2013). A change in the rate of SO 4 decrease is evident around [2005][2006][2007], with a general levelling off in concentrations in recent years.…”
Section: Pm 25 Particle Species (I) Major Ionsmentioning
confidence: 54%
See 2 more Smart Citations
“…In a subsequent examination of the method's internal optical data, Chen et al (2012) concluded that the transition's effects on longterm EC trends were generally minor. Comparable EC declines between 1999 and 2010 were reported by Blanchard et al (2013) for the SEARCH network in the southeast U.S.…”
Section: Absorption By Regional Haze Pm 25mentioning
confidence: 83%